Co-digestão anaeróbia de dejeto de suínos e penas de frango pré-tratadas para a produção de metano - Schommer, Vera Analise (2019)
Different substrates are investigated regarding the methane yield during anaerobic digestion (DA) and Co-DA. Swine manure and chicken feathers are abundant wastes from the meat supply chain. Although swine manure is employed in DA, feathers recalcitrance could affect this process. Pre-treatments might optimize biomass applications in Co-DA. This study aimed to evaluate methane production from fresh (DF) and matured (DM) swine manures added with feathers (with or without microbial pre-treatment). DF (diluted 1:2) and DM (diluted 1:1) were employed as inocula/main substrates in two experiments (Exp), DF and DM, respectively. Evaluated cosubstrates were fragmented feathers (PF) and feather hydrolysate produced by a keratinolytic bacteria (HP); sterilized DF was used as controls (C) to adjust the initial concentration of total solids (ST). In Exp DF, ST concentrations of 5.67% (1X) and 6.80% (2X) were evaluated; co-substrates represented 28.5% and 40.4% of ST, respectively. In Exp DM, ST concentrations of 4.6% (1X) and 5.1% (2X) were investigated; co-substrates represented 12.1% and 20,6% of ST. Co-DA were performed at 35 °C for 82-83 days. Methane production was measured through displacement of alkaline solution. Physico-chemical parameters were evaluated for inocula, co-substrates, and final products. In Exp DF, final methane production was not affected by 1X co-substrates (0.48 L CH4 (g SV)-1). For the 2X concentration, HP reduced methane production by 43% (0.28 L CH4 (g SV)-1) as compared to PF and C, possibly owing to elevated levels of ammonia nitrogen. PF (1X and 2X) has not affected final methane yield, although resulted in a transient decrease of this parameter. In Exp DM, methane production was superior for HP (1X and 2X; 0.16 and 0.19 L CH4 (g SV)- 1, respectively). However, PF (1X and 2X) resulted in the lower methane productions (0.12 and 0.16 L CH4 (g SV)-1), suggesting a decreased biodegradability. The modified Gompertz model displayed a better fit to describe the kinetics of methane production in the experiments when compared to the other three models tested. In summary, there is the possibility of using PF in Co-DA processes with DF/DM. HP concentration and inoculum were important factors for methane production, as observed by Co-DA inhibition with DF, and also due to the positive effect on methane yield with DM. The microbial pre-treatment of feathers represents a strategy to accelerate and increase methane production